Chondrosarcoma Skull Base: A Case Report - Bharti, Jyotsna N.; Elhence, Poonam; Bhaskar, Suryanarayanan; Garg, Pawan Kumar (Current Medical Imaging, 2023)
Introduction: Chondrosarcomas are primary malignant bone tumor that rarely occurs in the head and neck region. Squash cytology of skull base neoplasm shows atypical chondrocytes and myxoid stroma, which suggests many possibilities like chordoma, chordoid glioma, chordoid meningioma and chondrosarcoma. Isocitrate dehydrogenase gene (IDH) mutations have been reported in 50% to 60% of the head and neck region chondrosarcoma. Case Presentation: A 37-year-old female came to the outpatient department and complaint of difficulty in walking and swaying to the right side for one year. The radiology was suggestive of right-sided trigeminal schwannoma. However, the squash cytology showed the presence of necrosis, and pink to bluish-coloured myxoid stroma. The tumor cells were pleomorphic and had a hyperchromatic nucleus, hyalinized condensed to granular cytoplasm. The histopathological examination of intraoperative soft tissue showed the presence of cellular lobules of atypical chondrocytes arranged in the myxoid background. The features were of Chondrosarcoma. No parenchymal invasion was found. Conclusion: This case report aims to create awareness about a rare tumor, which rarely forms a differential diagnosis for skull base neoplasms. As chondrosarcoma are immunoreactive to IDH1 so this marker can be useful in clinching the diagnosis in conjunction with other immunohistochemical markers in a small biopsy from skull base neoplasms.
Keywords: the base of the skull